The total work of art : foundations, articulations, inspirations - Imhoof, David Michael, 1970-; Menninger, Margaret Eleanor; Steinhoff, Anthony J. (Spektrum (New York, N.Y.) ;, 2016)
"For two centuries, Gesamtkunstwerk-the ideal of the 'total work of art'-has exerted a powerful influence over artistic discourse and practice, spurring new forms of collaboration and provoking debates over the political instrumentalization of art. Despite its popular conflation with the work of Richard Wagner, Gesamtkunstwerk's lineage and legacies extend well beyond German Romanticism, as this wide-ranging collection demonstrates. In eleven compact chapters, scholars from a variety of disciplines trace the idea's evolution in German-speaking Europe, from its foundations in the early nineteenth century to its manifold articulations and reimaginings in the twentieth century and beyond, providing an uncommonly broad perspective on a distinctly modern cultural form."--Publisher description